39.9k views
1 vote
Simplify using the distributive property.

10 - 2(x - 7) = 4(x - 5)

24 - 2 x = 4 x - 20
-4 - 2 x = 4 x - 5
3 - 2 x = 4 x + 5

User Danypata
by
5.5k points

2 Answers

3 votes

Answer:

hey

Explanation:

User Hgpl
by
4.4k points
1 vote

Answer:x=22 over 3

Explanation:

Step 1: Simplify both sides of the equation.

10−2(x−7)=4(x−5)

10+(−2)(x)+(−2)(−7)=(4)(x)+(4)(−5)(Distribute)

10+−2x+14=4x+−20

(−2x)+(10+14)=4x−20(Combine Like Terms)

−2x+24=4x−20

−2x+24=4x−20

Step 2: Subtract 4x from both sides.

−2x+24−4x=4x−20−4x

−6x+24=−20

Step 3: Subtract 24 from both sides.

−6x+24−24=−20−24

−6x=−44

Step 4: Divide both sides by -6.

−6x−6=−44−6

x=22 over 3

hope it helps.

User Behnam Azimi
by
4.9k points